Salvage Reconstructive Surgery During Nivolumab Therapy for a Patient With Hypopharyngeal Cancer. Issue 13 (April 2020) - Tsushima, Nayuta; Shinozaki, Takeshi; Fujisawa, Takao; Tomioka, Toshifumi; Okano, Wataru; Ikeda, Masakazu; Tahara, Makoto; Higashino, Takuya; Hayashi, Ryuichi
Objectives: Nivolumab, a fully IgG4-programmed death-1 inhibitor antibody, led to improved overall survival compared with single-agent therapy in patients with platinum-refractory recurrent head and neck cancers. In general, nivolumab is used in inoperable patients. To the best of our knowledge, there have been no reports of salvage surgery during nivolumab therapy for patients with head and neck cancer. We report the case of a woman treated with salvage reconstructive surgery during nivolumab therapy. Method: Case report and literature review. Results: The patient underwent nivolumab therapy for recurrent primary and neck disease after induction chemotherapy, followed by concurrent chemoradiation therapy. The neck disease shrunk, whereas the primary disease temporarily shrunk but later progressed again. Recurrent primary disease led to a narrowing of her airway, and she required airway management. We performed total pharyngolaryngectomy with free jejunal reconstruction, and her quality of life improved. The surgery was performed without complications and the postoperative course was uneventful. She was discharged postoperative day 18 with oral intake function and a safer airway. Conclusion: As far as we know, this is the first report of salvage surgery during nivolumab therapy for patients with head and neck cancer. The salvage reconstructive surgery in this case proceeded uneventfully.